SOSTAC framework analysis for enhancing digital marketing in Yogyakarta's Art Music Today - Novi Anggraeni; Tussi Sulistyowati; Nur Elfi Husda (Journal of Community Service and Empowerment, 2024)
This research utilizes a qualitative descriptive methodology, employing the SOSTAC model to analyze Art Music Today (AMT). The study follows six structured steps, starting with a SWOT-based Situation Analysis highlighting AMT's strengths as a unique Yogyakarta entity. Strategic objectives are set using the 5s Framework, focusing on digital marketing elements like online sales optimization and user experience. The Strategy phase emphasizes STP marketing, presenting AMT as a tailored music information center. Tactics, guided by the 7P framework, include product diversification and pricing strategies, contributing to an enhanced user experience. An 18-month action plan, depicted in a Gantt chart, guides implementation from content creation to streamlined processes. The Control phase involves monitoring with Google Analytics and social media evaluation. Through leveraging strengths and addressing weaknesses, AMT positions itself for growth in the digital landscape, using the SOSTAC model as a robust framework for digital marketing excellence.  As a suggestion, through a proactive approach to leveraging inherent strengths and addressing weaknesses, AMT aims for significant growth in the dynamic digital environment. Aligning its digital marketing efforts with the SOSTAC model, which covers Situational Analysis, Objectives, Strategy, Tactics, Action, and Control, ensures a comprehensive understanding of current market dynamics. This strategic alignment establishes the foundation for a well-defined and actionable digital marketing strategy.